Peningkatan Keterampilan Bahasa Anak dalam Komunikasi Melalui Media Boneka Tangan - Vina Rahmatika; Nurul Ismaiyah; Masruroh Masruroh; Ummu Kulsum; Syarif Hidayatulah; Diah Meilani Silvita; Jannatul Munawarah (Child Kingdom : Jurnal Pendidikan Anak Usia Dini, 2025)
The aim of this study is the improvement of children's language skills in communication through hand puppet media in group A of RA As-Syuhada' Pamekasan. The problem behind the research is the low communication skills of the children, which is indicated by the lack of confidence in public speaking, difficulty in expressing opinions, and limited ability to interact with peers. This research method is a classroom action research (PTK) in two cycles. The research subjects were 37 children in group A. Data collection was done through observation, documentation and anecdotal records. The research instrument included an observation sheet. The results showed a significant improvement from cycle I to cycle II. In Cycle I, only 30% of the children reached the minimum criteria of "good". After the improvement in learning in Cycle II, the percentage of children reaching the "Good" criteria increased to 90%, exceeding the success standard set at 75%. This increase was achieved through improved learning strategies which included variations in storytelling, the use of more interesting media and the creation of an interactive learning atmosphere. The results of this study conclude that the use of puppet media is effective in improving children's communication skills. This success is not only reflected in the aspect of verbal communication, but also in the increase of children's self-confidence and socialisation skills.